2015
DOI: 10.1016/j.bbalip.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic and proteomic analysis of Caenorhabditis elegans lipid droplets and identification of ACS-4 as a lipid droplet-associated protein

Abstract: Lipid droplets are cytoplasmic organelles that store neutral lipids for membrane synthesis and energy reserves. In this study, we characterized the lipid and protein composition of purified C. elegans lipid droplets. These lipid droplets are composed mainly of triacylglycerols, surrounded by a phospholipid monolayer composed primarily of phosphatidylcholine and phosphatidylethanolamine. The fatty acid composition of the triacylglycerols is rich in fatty acid species obtained from the dietary E. coli, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 59 publications
5
94
0
Order By: Relevance
“…3, Table S1). This diversity of lipid droplets-associated protein was also observed in earlier reported proteomics studies of multiple species, including oleaginous bacterium24, green algae35, Drosophila 2728, C. elegans 25, adult mice19 and mammalian cells26. The number of enzymes present in lipid droplets is greater in mice than in P. brassicae 19, which is greater in P. brassicae than that of the oleaginous bacterium PD63024.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…3, Table S1). This diversity of lipid droplets-associated protein was also observed in earlier reported proteomics studies of multiple species, including oleaginous bacterium24, green algae35, Drosophila 2728, C. elegans 25, adult mice19 and mammalian cells26. The number of enzymes present in lipid droplets is greater in mice than in P. brassicae 19, which is greater in P. brassicae than that of the oleaginous bacterium PD63024.…”
Section: Discussionsupporting
confidence: 76%
“…14 enzymes were involved in lipid synthesis and degradation, including 3 transferases, 2 ligases, 7 dehydrogenases, 1 reductase and 1 synthase. 83 enzymes were involved in metabolic processes, while 28 were involved in biosynthetic processes ribosome, chaperone and histone proteins are abundant in the lipid droplets of P. brassicae , which had been identified in the lipid droplet proteomes of oleaginous bacterium24, Caenorhabditis elegans 25, mammalian cells26, adult mice19 and Drosophila embryos2728. Rab GTPase29, dynein, kinesin30, kinesin motor domain containing protein, actin31, 14-3-3 signaling proteins17 and heat shock protein 7032 were previously reported to play important roles in maintaining the functions of lipid droplets, and these proteins were identified in the lipid droplets proteome of P. brassicae .…”
Section: Resultsmentioning
confidence: 99%
“…Although the reduced fat accumulation may be due to reduced yolk production, an alternative interpretation is that vitellogenins play a role in intracellular lipid transport. VIT-2 was recently identified as a lipid dropletassociated protein Vrablik et al 2015), and here we found that iron promoted the accumulation of VIT-2 protein in LDs (Figure 5,D and E). Meanwhile, the expression of VIT-2::GFP is also brighter in cyp-23A1(gk253) mutant, but not in acs-20(tm3232) mutants compared to N2 regardless of treatment with FAC ( Figure S9).…”
Section: Discussionmentioning
confidence: 52%
“…The expression of VIT-2::GFP is also brighter in cyp-23A1(gk253) mutant, but not in acs-20(tm3232) mutant compared to N2 under both FAC treatment and no FAC (Figure S9). VIT-2 is a yolk lipoprotein, but it has also been reported to be a C. elegans lipid droplet-associated protein Vrablik et al 2015). After isolating lipid droplets and other cellular fractions of vit-2::gfp worms treated with FAC 0 and 5.0 mg/ml, Western blot analysis using anti-GFP antibody showed that the level of VIT-2 protein was significantly increased in LD, total membrane (TM), and postnuclear supernatant (PNS) under FAC 5.0 mg/ml compared to FAC 0 mg/ml ( Figure 5, D and E).…”
Section: Vit-2 Translocates Dietary Lipids To Lipid Dropletsmentioning
confidence: 99%
“…Lipidomics reveals that the core of an LD can contain over 100 different species of neutral lipids [22-26]. This repertoire is sure to expand over the next few years with the development of increasingly sophisticated lipidomics methods as well as imaging techniques based on Raman and mass spectrometry [27-34].…”
Section: 0 Lipid Droplets and Lipid Handlingmentioning
confidence: 99%